Sustainability reporting disclosure practices among Bangladeshi companies in line with Global Reporting Initiatives - Das, Sumon Kumar; Miah, Masum; Miah, Md. Rubel; Akter, Diljahan; Hossain, Tanvir (Asian Journal of Accounting Perspectives, 2021)
Research aim: The core objective of this study is to identify the nature and extent of sustainability reporting disclosure practices among Bangladeshi listed companies, in line with global reporting initiatives (GRI). Design/Methodology/Approach: The content analysis method is used in this study to examine a total of 48 items, consisting of 17 environmental and 31 social disclosure items, in line with GRI. Data were drawn from the published annual reports of a sample of 51 listed companies for the financial year of 2016/2017. Research findings: On average, 13.73% of the sample companies did not disclose any issue on sustainability reporting. The overall sustainability reporting index of these companies is 10.70% (environmental: 11.42% and social: 10.31%). The level of overall disclosure is low, with the Cement industry focusing on both social (21.18%) and environmental (14.19%) areas, the Textile industry mainly focusing on the environmental (17.06%) area, and the Bank industry mainly focusing on the social (25.16%) area. There is a paucity of disclosure of both social and environmental issues in Food & Allied and Pharmaceuticals & Chemicals industries. Companies are reluctant to disclose issues related to emission, effluent, waste, and compliance under the environmental dimension, and human rights and social performance indicators under the social dimension. Theoretical contribution/ Originality: Several studies have been conducted on either corporate social reporting or environmental reporting, but there is a dearth of an integrated investigation into the level of sustainability reporting practices in Bangladesh. This study enumerates the sustainability reporting practices in Bangladesh based on the most recognised global non-financial reporting standard, namely GRI. Practitioner/ Policy implication: With the growing awareness among stakeholders and the initiatives taken by regulators, there might be an increasing trend in sustainability reporting practices. This study is expected to contribute to the introduction of more regulatory requirements for a comprehensive framework on sustainability reporting. Research limitation: This study focuses on only quantity and not quality in preparing the disclosure index and considers only one period. Keywords: Social Reporting, Environmental Reporting, Sustainability Reporting, Global Reporting Initiatives, Bangladesh Type of Manuscript: Research paper JEL Classification: M14